2020
DOI: 10.2169/internalmedicine.3726-19
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor Can Reduce HCV-RNA without Liver Damage

Abstract: Recently, immune checkpoint inhibitors (iCIs) have been used to treat cancers. Once some of the iCIs for the treatment of hepatocellular carcinoma (HCC) are certified in clinical trials, they are likely be administered to HCC patients with hepatitis C virus (HCV). However, the immunopathogenesis of HCV after the administration of iCIs has not been clarified. We experienced a lung cancer patient with HCV infection treated by nivolumab, programmed cell death 1 (PD-1) antibody. HCV-RNA gradually decreased after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…ICIs-related hepatitis could be critical for patients of hepatocellular carcinoma (HCC) since many HCC patients could have limited liver function due to the liver cirrhosis. Previously, we reported that various kinds of factors including hepatitis B virus, hepatitis C virus, and the HCC microenvironment might affect the immune pathogenesis of liver diseases [18][19][20][21][22][23][24] . In this study, we included 3 HBsAg positive inactive carrier.…”
Section: Discussionmentioning
confidence: 99%
“…ICIs-related hepatitis could be critical for patients of hepatocellular carcinoma (HCC) since many HCC patients could have limited liver function due to the liver cirrhosis. Previously, we reported that various kinds of factors including hepatitis B virus, hepatitis C virus, and the HCC microenvironment might affect the immune pathogenesis of liver diseases [18][19][20][21][22][23][24] . In this study, we included 3 HBsAg positive inactive carrier.…”
Section: Discussionmentioning
confidence: 99%
“…Although PD-1 is a marker of exhaustion on T cells, it is also a marker of T cell activation. Dysfunctional CD8 + T cells and activated CD8 + T cells up-regulate genes involved in activation of the cell cycle, T cell homing and migration, as well as effector molecules, such as granzymes and co-stimulatory and co-inhibitory receptors [ 60 ]. In fact, the PD-1 high expression on HCV-specific T cells during acute infection do not correlate with the clinical outcome, suggesting that the PD-1 level is marking activation but not exhaustion during acute hepatitis [ 61 ].…”
Section: Pd-1 Modulation For T Cell Exhaustion Reversionmentioning
confidence: 99%
“…HCV-specific CD8 T cells targeting HCV epitopes during persistent infection become exhausted and expresses several negative IC, such as PD-1 [ 18 ]. Different in-vitro studies have shown that the PD-1/PD-L1 blockade can restore T cell reactivity in some patients [ 43 , 72 ] and, there are also clinical evidences that blocking this pathway could lead to HCV control [ 60 , 73 ]. Nevertheless, a bulk of HCV patients are not responders to this immune modulation.…”
Section: Effect Of Pd-1 Modulation and γC-cytokines On Hcv-specifimentioning
confidence: 99%
“…A case report published by Fukuda et al (2020) demonstrated a case of HCC with a decline in HCV RNA after administration of anti-PD-1 antibody (nivolumab). HCV-RNA titers decreased, without liver damage, after the initiation of treatment with nivolumab; the decline in HCV RNA titers was observed regardless of the antitumor effect [ 63 ].…”
Section: Immunotherapymentioning
confidence: 99%